Factors Influencing Gen-Z’s Purchase Intention as Consequences of Product Placement Practice in K-Drama - Janice, Janice; Rosa, Tamara; Widjojo, Handyanto; Amelia, Novi (Kajian Branding Indonesia, 2025)
This study aims at investigating how scarcity, demand, convenience, interactivity, and playfulness affect impulsive purchasing on live streaming e-commerce. This article explores how limitation in quantity, limitation of time, convenience, and interactiveness affect perceptions about arousal, enjoyment, and impulsive buying. In orderto achieve understanding in relation to how mental processes result in emotional outcomes leading to impulse purchase, this study adopts the S-O-R model theory of Mehrabian and Russell (1974). This is a quantitative research work that involves surveyed data collection and statistical analysis. With the assumption of indicationregarding limited time scarcity, limited quantity scarcity, demand, convenience, interactivity, playfulness, perceived arousal, and perceived enjoyment are related to impulsive purchase behavior. This study aims to support the validity and enhancement of the S-O-R model such that its use in explaining e-consumer behavior can be justified. Therefore, these implications for business will help them build marketing and branding strategy, promotion campaigns, product launches, live shopping events, and create loyal customers with return purchases. This study concludes that it is necessary to understand how scarcity, convenience, and interactivity affect spontaneity buying process in live selling electronic platforms and more studies should be done into this field.